Exploring potential political corruption in large-scale infrastructure projects in Nigeria - Olugboyega Oluseye (Project Leadership and Society (PLAS), 2024)
Political corruption is especially relevant for large-scale projects because of their popularity among politicians and citizens alike, as well as their inherent qualities. The goal of this study is to find out about the causes, methods, occurrences, and effects of political corruption in large-scale infrastructure projects in Nigeria. The investigation uses a case analysis of Lagos-Ibadan Highway and was divided into two stages: the 1999-2009 political era and the 2010-2019 political era. The information was gathered through document and report analysis. The symptomatic investigation of the political corruption of the Lagos-Ibadan Highway was guided by a conceptual model based on symptoms. Within-case and cross-case comparative theme analysis were performed on the dataset. The investigation indicated how the occurrence of patronage, influence peddling, embezzlement, and biased law enforcement can explain political corruption in the highway project. The investigation resulted in a better understanding of the reasons for the project's failure and abandonment. The knowledge can be used to prevent political corruption in public projects and to lay the groundwork for long-term infrastructure development. This study was limited because it was unable to provide unambiguous evidence to prove that political corruption occurred in the case study.
Keywords: 650; Corruption; Infrastructural projects; Political corruption; Project success; Sustainable infrastructural projects